Cerebral Amyloid Angiopathy Related Inflammation With Prominent Meningeal Involvement. A Report of 2 Cases - Aghetti, Agnès; Sène, Damien; Polivka, Marc; Shor, Natalia; Lechtman, Sarah; Chabriat, Hugues; Jouvent, Eric; Guey, Stéphanie (Frontiers in Neurology, 2019)
Cerebral amyloid angiopathy related inflammation (CAA-RI) is a rare form of CAA characterized by subacute encephalitic symptoms (cognitive decline, seizures, focal deficits) characterized on brain MRI by extensive and confluent white matter lesions colocalizing with lobar microbleeds. We report two cases of unusual CAA-RI mimicking meningoencephalitis without typical brain lesions on FLAIR and T2* sequences, which diagnoses were delayed. These 2 cases may extend the spectrum of CAA-RI by suggesting the possible occurrence of quite purely meningeal forms of CAA-RI.